Optimisation of electrospinning parameter for Poly(L -lactic) acid (PLLA) electrospun nanofiber - Marini, Sawawi; Siti Kudnie, Sahari; Kuan, Nicholas; Mahshuri, Yusof; Magdalene, Andew; Salleh, Sf; Rohana, Sapawi (EDP Sciences, 2016)
Poly (L-lactic) Acid (PLLA) ia one of the biodegradable polymer that normally used in the biomedical application. In this work it is shown that electrospinning of PLLA electrospun fibre was affected by electrospinning processing parameters such as the solvent systems selection, polymer solution concentration, flow rate and acceleratingvoltage. Optimisation of these parameters is necessary to obtain a beadless and submicron diameter fibre as desired in this research